Las Primeras Etapas en la Formación de una Galxia - Deaza Rincón, Pedro Ignacio (Ingeniería, 2004)
It is an article in which is used the virial theorem scalar, for study of a great cloud isotherm, of constant mass, that contracts in a process adiabatic, imbibed in a medium of very low density, hot and of negligible gravity, compared with the gravity of the cloud and in presence of a magnetic field uniform, that could vary but of like manner that the magnetic flow stays constant. A general expression for the external necessary pressure for the collapse in function of the equatorial radio is deduced for the cloud, in which is present the magnetic field, the eccentricity and the size of the cloud. The analysis of the expression drives to establish the conditions of equilibrium of the cloud and the circumstances in those that one could unchain a gradual contraction that drives inevitablement it even collapse gravitational.